China : isu dan hubungan luar - Obaidellah Mohamad; Universiti Malaya. Institut Pengajian China (Kuala Lumpur : Institut Pengajian China, Universiti Malaya, 2004)
Issues on international and foreign relations of China; collection of articles
Includes bibliographical references
In Malay
Koleksi sumbangan Prof. Dr. Ding Choo Ming.
Keywords: China -- Foreign relations -- 1976-; China -- Politics and government -- 1976-2002; China -- Politics and government -- 2002-